The Heart Team, TAVI and natural selection - Doubell, Anton (SA Heart Journal, 2017)
The announcement in 2002 that Alan Cribier had performed the first Transcatheter Aortic Valve Implantation (TAVI) ranked right up there with the announcement that the first heart transplant had been performed by Chris Barnard, or the announcement that Andreas Gruentzig had performed the first coronary angioplasty. At the time we rightly viewed this as an exciting breakthrough in the management of patients with aortic stenosis and had little reason to anticipate that perhaps the major challenge for TAVI still lay ahead.